Integral technologies of psycho-physical training of athletes in sports aerobics - Tetiana Shepelenko (Kharkiv State Academy of Physical Culture, 2017)
Purpose: substantiate the use of integral technologies for the psycho-physical training of athletes in sports aerobics. Material & Methods: 46 qualified aerobics participated in the study, 22 athletes made up a control group, 24 were experimental, and 19 aerobists, 9 athletes made up an experimental group, 10 were a control group. Methods: theoretical analysis of literature data; method for evaluating the results of competitive activities; pedagogical experiment; methods of mathematical statistics with the use of computer programs "EXEL" and "SPSS". Results: psychophysical training should be one of the main parts of the variable component of the general training program for aerobic athletes. It is based on the implementation of special sets of exercises in conjunction with mental imagery of the nature of the movements. The positive effect of the use of integral technologies of psychophysical training on the competitive performance of athletes. Conclusion: construction of the training process with the use of integral technologies of psychophysical training had a positive effect on the effectiveness of the competitive activity of athletes.